The first disease centred network in Spain: a bottom-up cardiovascular hospital and primary care network focused on reducing variability, improving population health and efficiency. (25th November 2020) - Bengoa Terrero, C; Bas Villalobos, M; Macaya Miguel, C; Maroto Castellanos, L.C; Fernandez Rozas, I; Garcia Lledo, A; Perez Villacastin, J
Abstract: Introduction: In an autonomous region in Spain, the heads of cardiovascular disease from four hospitals, forty-three primary care centres and the ambulance provider, have come together to collectively reduce variability, improve outcomes and patient experience, increase efficiency and focus on population health through prevention. As a result, a cardiovascular network was founded to address the needs of the population through eight projects, each with a group of professionals dedicated to its completion. This region has Beveridge-type universal healthcare and the clinical network must operate under a choice model in which patients can choose where they wish to be treated. This approach has never been carried forward in Spain previously nor, as far as we are aware, in Europe from the bottom-up with clinical leaders achieving buy-in from the political level. Purpose: With the well-known demographic challenge putting the system under strain, our hypothesis is that this innovative collaborative approach where by hospitals pool resources and implement collective improvements from the bottom-up will results in better health for its population of over one million people. Methods: The Institute for Healthcare Improvement's Assessment Scale for Collaboratives is used to track project progress through the valuation of project leads assigned to each project and the senior project manager. This scale divides progress from: forming team, activity but no changes, modest improvement, significant improvement, and outstanding sustainable results; some are further subdivided as shown in the image. Projects each have their set of indicators to ensure project objectives are achieved. Results: The network has 8 working projects which include different specialists, professional groups and organizations including primary care and the main ambulance provider. The four hospitals have pulled together their resources to recruit two project managers. Progress measured with the Assessment Scale for Collaboratives indicates that projects have moved forward 18% in a three month period, reaching an average progress of 35%. Conclusion: The closer collaboration across four hospital sites has put this network at the forefront of Spanish health policy by focusing work on diseases rather than by geographical areas. This allows clinical leaders to decide and focus on objectives that most suit the needs of its population whilst building a culture of continuous improvement across multiple care sites and professional groups. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Fundaciόn Interhospitalaria para la Investigaciόn Cardiovascular - Fundaciόn FIC